Identification of Signalling Pathways Regulating Autophagy in Response to Cellular Stress - Alsaadi, Reham (Université d'Ottawa / University of Ottawa, 2025)
Macroautophagy (hereafter referred to as autophagy) is a key cellular degradative process that plays an important role in maintaining cellular homeostasis. Defects in autophagy are linked to a range of health conditions, including but not limited to metabolic disorders, inflammatory bowel diseases, and cancer. Despite decades of research, measurement of autophagy dynamics in rare cell populations and in vivo remains challenging due to the inherent limitations of existing tools. We developed a novel approach for autophagy measurement by monitoring the phosphorylation of ATG16L1 on serine 278 (pATG16L1ˢ²⁷⁸). We found that phospho-ATG16L1 is exclusively localized to nascent autophagosomes, and that its detection is not confounded by prolonged cellular stress or late-stage autophagy impairments, which often obscure autophagic analyses. We have developed and characterized a monoclonal antibody capable of specifically detecting endogenous phospho-ATG16L1 in mammalian cells. This highly versatile antibody enables its use in Western blotting, immunofluorescence, and immunohistochemistry assays for autophagy measurement. In the context of metabolic disorders, we investigated the impact of chronic iron overload on the autophagy pathway. Iron overload is a clinical hallmark of metabolic syndrome, which is a collection of conditions often associated with insulin resistance and is known to lead to increased risk of developing cardiovascular disease and type 2 diabetes. We discovered that chronic iron overload induced major autophagy disruptions, as evidenced by the accumulation of defective autolysosomes and a significant depletion of free lysosomes in skeletal muscle cells. The autophagy defects, in turn, led to impairment of insulin-stimulated glucose uptake and disrupted insulin signaling. Mechanistically, we demonstrated that iron overload affected Akt-mediated suppression of tuberous sclerosis complex 2 (TSC2) and reduced Rheb-dependent activation of mechanistic target of rapamycin complex 1 (mTORC1) on autolysosomes. This dysregulation inhibited the autophagic‐lysosome regeneration, thereby contributing to the development of insulin resistance. Notably, restoring mTORC1 signaling to the autophagy machinery on mature autophagosomes, or removing excess iron, significantly replenished lysosomal pools and restored insulin sensitivity. This discovery uncovers the potential therapeutic pathways that could be targeted to improve insulin sensitivity in metabolic syndrome. Additionally, we examined the process of ER-phagy, which is the selective degradation of the endoplasmic reticulum (ER) by autophagy. ER-phagy is critical for maintaining cellular homeostasis and is frequently targeted by pathogens to create a more favourable cellular environment for infection. We discovered that Salmonella Typhimurium utilizes a mechanism to inhibit ER-phagy by targeting the ER-phagy receptor FAM134B. This inhibition prevents FAM134B oligomerization, a key step in the ER-phagy pathway, leading to increased intracellular bacterial load post-invasion. In FAM134B knockout mice, we observed increased susceptibility to Salmonella infection, characterized by severe intestinal damage and elevated bacterial loads. Furthermore, we identified the bacterial effector SopF as the primary mediator of FAM134B inhibition, shedding light on how intracellular bacteria such as Salmonella could subvert innate immune defenses. Together, these studies provide a comprehensive understanding of the complex regulatory networks that govern autophagosome biogenesis, maturation, and functionality. They also highlight the critical role of environmental factors in modulating autophagic activity and maintaining cellular homeostasis, revealing the dynamic interplay between intracellular mechanisms and external stimuli in the regulation of autophagy. Identifying novel therapeutic targets, such as phospho-ATG16L1 and FAM134B, offers promising avenues for developing interventions to restore autophagy and mitigate disease progression.
Keywords: Autophagy; ERphagy; Salmonella; Iron; ATG16L1; Insulin